A SOCIOLINGUISTIC STUDY OF GENDERED LANGUAGE IN JAMAICA KINCAID’S ‘GIRL’ USING SPEECH ACT THEORY AND DEFICIT MODEL - Fatah, Shokhan Mohammed; Muhammed, Areen Ahmed (Universitas Islam Sumatera Utara (UISU), 2025)
This paper examines gendered language in Jamaica Kincaid’s (born 1949) short story ‘Girl’ through J. L. Austin’s Speech Act Theory and Robin Lakoff’s Deficit Model. Structured as a monologue of maternal instructions, the narrative provides a lens to analyze language’s performative function in reinforcing authority, dependency, and gender norms. Applying Speech Act Theory, the study explores how directives, warnings, and illocutionary acts preserve traditional femininity and power relations. Simultaneously, it engages with the Deficit Model to demonstrate how women’s language is positioned as less assertive, shaping the daughter’s social identity. Using qualitative content analysis, the study examines linguistic features and speech acts to identify patterns of gendered language and power dynamics. Findings reveal that the mother’s speech acts, particularly commands and warnings, function as tools of linguistic control, reinforcing patriarchal ideologies and expectations. The paper highlights the role of language in shaping female identity through authoritative discourse, demonstrating how speech acts contribute to sustaining social hierarchies. By offering a nuanced exploration of gendered linguistic structures, this research contributes to sociolinguistic and literary discourse, deepening the understanding of power, identity, and representation in literary texts. The work underscores how language encodes and perpetuates gendered ideologies, adding to broader discussions on discourse, power relations, and identity formation in literature.